Definition of a data model that includes the instructional design to describe the elements involved in the design of virtual courses - Perea, Betsy Mary Estrada (My University, 2016)
Conventional software engineering methodologies have strategies for analysis and design of educational software applications, but they have evolved in relation to the phase of the instructional design. In this article, from the review of some models of instructional design and the identification of gaps in two proposed models for the design of virtual courses, a data model is proposed to describe the elements involved in the design of virtual courses and illustrate the relationships between such elements. In preparing this model, we take into account the activities of some models of instructional design. The construction of this data model is a contribution to formalize the design of virtual courses.
Keywords: Modelo de datos; Diseño instruccional; Cursos virtuales